2021
DOI: 10.5935/1980-6906/eptppa13041
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Perceptions of Academic Stress Scale

Abstract: No momento em que escrevo este editorial, o Brasil (e o mundo) atravessam um doloroso ressurgimento da Covid-19. Não refeitos dos seus múltiplos impactos negativos -especialmente em termos de saúde mental -, somos novamente chama-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Third, with little variation captured for depressed HE students, this group should receive independent focus to identify relevant explanatory pathways, as well as to reveal potential avenues for HE support and intervention. Fourth, this study assessed academic stress via four relevant stressors, although additional sources of academic stress are found among students, including time constraints, parental pressures, teachers' expectations, and self-perceptions ( 78 , 79 ). As such, further study including additional sources of academic stress will serve to improve understanding of the collective and independent effects of academic stressors on student wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Third, with little variation captured for depressed HE students, this group should receive independent focus to identify relevant explanatory pathways, as well as to reveal potential avenues for HE support and intervention. Fourth, this study assessed academic stress via four relevant stressors, although additional sources of academic stress are found among students, including time constraints, parental pressures, teachers' expectations, and self-perceptions ( 78 , 79 ). As such, further study including additional sources of academic stress will serve to improve understanding of the collective and independent effects of academic stressors on student wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…In the Nigerian context, the scale was found to be reliable (0.79) for this study. França and Tatiane [ 54 ] reported 0.83 reliability using Portuguese populations.…”
Section: Methodsmentioning
confidence: 99%
“…SR includes students' ability to set academic goals and plan how to achieve them through the use of speci c learning strategies [41] [42], such as self-monitoring and self-evaluating their successes and failures and consequently regulating their mindset and behavior to accomplish their goals [43]. A sizable number of studies have shown that self-regulation and the ability to manage one's own behavior can assist learners in coping with academic stress, thus preventing long-term negative consequences [44]. Many research articles have demonstrated a negative association between academic stress and self-regulation among undergraduate students [44] [45] [46] [37].…”
Section: The Potential Mediating Role Of Self-regulationmentioning
confidence: 99%